Implementasi Google Classroom Pada Perkuliahan Mahasiswa Semester 2 Pendidikan Matematika ITSNU Pasuruan - Mardhiana, A’inaul; Linda, Lutviah Mardah; Khoirunnisa’, Iis (Jurnal Likhitaprajna, 2023)
Access via the internet to use Google classroom while they lack data packages and unaffordable signals and networks where they live and confusion to use features on Google classroom because it is the first time using. The method used is a qualitative research method with a field research approach and is analytically descriptive. The data collection techniques are using documentation, observation and data collection through questionnaires to several ITSNU Pasuruan semester 2 mathematics education study program students related to the use of Google Classroom in the lecture process. Google Classroom is very useful in the lecture process of ITSNU Pasuruan students. This platform makes it easier for lecturers and students to interact and collaborate online, increase student involvement in the learning process, facilitate the management of assignments and grades, and strengthen students' understanding of information technology. In addition, Google Classroom can also save students' time and transportation costs because they can access lecture materials without having to physically attend class. Therefore, Google Classroom is highly recommended as one of the virtual learning platforms that can help improve the quality of learning process in the future. In the management of online lecture learning, it should be done by involving the help of guidance to use the application at the beginning of the lecture and finding solutions for students whose residence is in remote areas due to the absence of signal which results in hampering online lectures.